2015
DOI: 10.1515/rput-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation Of Polysacharides And Lipids From Selected Green Algae Species By FTIR-ATR Spectroscopy

Abstract: Fourier transform infrared (FTIR) spectroscopy was used in this study to identify and determine spectral features of Chromochloris zofingiensis (Dönz) Fucíková et L.A.Lewis Gottingen, Germany), Acutodesmus obliguus (Turpin) Hegewald Gottingen, Germany) and Chlorella sorokiniana (K. Brandt) Pröschold et Gottingen, Germany). Polysaccharides and lipids from these three algae species were determined using Fourier Transformed Infrared Spectroscopy (FTIR) with ATR accessory with diamante crystal in spectral ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
(7 reference statements)
1
9
0
Order By: Relevance
“…The vibration intensity, reported as absorbance, is proportional to the relative abundance of organic molecules such as carbohydrates, lipids, and proteins [48]. The FTIR spectra analysis of GS provides interesting information about the changes in the macromolecule composition induced by different growth conditions, confirming the usefulness of FTIR as a fast, non-disruptive method to identify macromolecules in microalgae [49,50]. The intensity of the peaks corresponding to proteins, lipids, and carbohydrates was greater in HGS than in AGS and Sp, with the only exception with the peak observed around 1540 cm −1 , which was higher in Sp and AGS, and was ascribable to N-H stretching of proteins.…”
Section: Infrared Spectrophotometrymentioning
confidence: 88%
“…The vibration intensity, reported as absorbance, is proportional to the relative abundance of organic molecules such as carbohydrates, lipids, and proteins [48]. The FTIR spectra analysis of GS provides interesting information about the changes in the macromolecule composition induced by different growth conditions, confirming the usefulness of FTIR as a fast, non-disruptive method to identify macromolecules in microalgae [49,50]. The intensity of the peaks corresponding to proteins, lipids, and carbohydrates was greater in HGS than in AGS and Sp, with the only exception with the peak observed around 1540 cm −1 , which was higher in Sp and AGS, and was ascribable to N-H stretching of proteins.…”
Section: Infrared Spectrophotometrymentioning
confidence: 88%
“…Infrared spectroscopy can identify the functional groups contained in a molecule (Zhang et al 2020). Dhivya et al (Dhivya 2017) have reported that the change of O-H may be related to the production of polyphenols and avonoids, and another study shows that phenolic compounds and avonoids are considered antioxidants and can be used as reducing agents and free radical scavengers (Gupta and Gupta 2011) Bartošová 2015) showed that 1644 cm − 1 is the characteristic band of protein spectrum. Yu et al (Yu et al 2020) analyzed infrared spectra and found that the absorbance of high concentration of Cd in the roots is greater than that of low concentration at the absorption band of 1631 cm − 1 -1637 cm − 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The peak at 1,645 cm À1 -1,623 cm À1 was assigned to C ¼ O stretching. The absorption band ranged from 1,404 cm À1 to 1,391 cm À1 could be assigned to C-O bending from carboxylate ions (Bartošová et al 2011). The band in the region from 1,100 cm À1 to 1,000 cm À1 in two samples might be characteristic of C-O stretching of carbohydrates (Zhao et al 2014).…”
Section: Ftir Analysismentioning
confidence: 94%